Evaluating NATO Enlargement: From Cold War Victory to the Russia-Ukraine War, edited by James Goldgeier, and Joshua R. Itzkowitz Shifrinson. Palgrave Macmillan, Cham, 2023. XVII, 645 pp. https://doi.org/10.1007/978-3-031-23364-7 - Svetlana Jilavyan; Magda Arsenyan (Journal of Political Science: Bulletin of Yerevan University)
This book examines the main stages and authoritarian obstacles of NATO enlargement in Central and Eastern Europe after the Cold War, which gradually transformed into a hybrid conflict. In the various chapters of this book, the authors compare the main advantages and disadvantages of NATO enlargement in terms of the results of defending democratization in Central and Eastern Europe. The authors analyze the relationship between NATO enlargement and U.S. foreign policy on democracy and security in Central and Eastern Europe, which are indicators of NATO’s resilience as a political and military intergovernmental organization. The book analyzes the challenges of democratizing political regimes from the perspective of political security, including the full-scale Russian-Ukrainian war of 2022.